Social tourism and well-being in a first nation community. (July 2019) - Pyke, Joanne; Pyke, Sarah; Watuwa, Richard
Abstract: This paper examines the effects of social tourism on a First Nation community. Hypothesizing that social tourism promotes self-reported subjective well-being (SWB), we conducted an experiment to analyze the SWB effects of a one-day trip on low-income families from a First Nation community. Confirming our hypothesis, results show improved SWB mean scores in four of six domains: namely family relations, social life, material well-being, and leisure. Results also demonstrate that SWB effects are shaped by gender and age. These results have significant implications for policy related development, particularly in regard to First Nation and low-income communities. Moreover, this study is the first to apply social tourism theory to a First Nation community, making its results and implications unique. Highlights: Few have explored benefits of social tourism on individual well-being in Aboriginal communities. An experimental study of social tourism benefits for travelers and non-travelers is examined. Positive changes in subjective well-being for a low-income group are revealed. Even trips of short duration have significant effect on well-being, especially family relations. Study results advance the need to integrate social tourism in public policy.